Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information - Heleodoro, Raphael Aquino; Mendes, Diego Matheus De Mello (Zootaxa, 2016)
Lutosa horribilis sp. nov., a new species of Anostostomatidae is described from a Brazilian Atlantic Forest environment. Notes on defensive behavior and diet are also provided.